2017
DOI: 10.1155/2017/4646789
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Chemical Modification of Dental Enamel Submitted to 35% Hydrogen Peroxide “In-Office” Whitening, with or without Calcium

Abstract: Purpose The purpose of this study was to evaluate changes in calcium and phosphorus content in dental enamel when subjected to “in-office” whitening for an extended time by using a 35% hydrogen peroxide solution, with and without calcium. Materials and Methods 10 human teeth, from which the roots had been removed, were embedded in epoxy resin, and their surfaces were smoothed. The specimens were divided into two groups; in group 1, a whitening solution without calcium was used, while in group 2, the solution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
2
10
0
1
Order By: Relevance
“…Tooth bleaching, regardless of the bleaching agent concentration and frequency of application, did not increase enamel surface no matter how excessively they were used [25]. Also studies that analyzed surface roughness showed no statistically significant difference between bleached and unbleached enamel when using home bleaching agents [15].…”
Section: Discussionmentioning
confidence: 94%
“…Tooth bleaching, regardless of the bleaching agent concentration and frequency of application, did not increase enamel surface no matter how excessively they were used [25]. Also studies that analyzed surface roughness showed no statistically significant difference between bleached and unbleached enamel when using home bleaching agents [15].…”
Section: Discussionmentioning
confidence: 94%
“…Salomão et al 22 evaluated the susceptibility to demineralization of bleached dental enamel subjected to different fluoride application regimes and showed that the use of hydrogen peroxide and carbamide peroxide (CP), both at 35%, should be associated with a daily enamel fluoridation, otherwise, the in-office dental bleaching turn the tooth enamel more susceptible to demineralization. Therefore, the presence of calcium and/or fluoride in the bleaching gel composition, has the purpose of reducing the possible deleterious effects caused by high concentrated dental bleaching gels, in order to increase the incorporation of minerals into the dental enamel in an attempt to reduce adverse effects to the hydroxyapatite crystals 27,28 .…”
Section: G1 -Sevenmentioning
confidence: 99%
“…Although there are protocols that reduce the contact time between the bleaching agent and the tooth structure, there are several adverse effects found in the literature, the most common being tooth sensitivity [4,9,11,12,, which is generally associated with the ability of hydrogen peroxide to diffuse rapidly through enamel and dentin and penetrate the pulp, causing intense damage [3,9,17,19,20], as pulp inflammatory reactions [11,19,21], reduced cell proliferation and reduced pulp repairing capacity, which can lead to reversible pulpitis or even tissue necrosis [3,14,22]. Morphological changes in enamel and dentin and changes in mineral content can also occur resulting in the presence of erosions, porosities (which can lead to possible bacterial colonization), 23 decreased microhardness and nano hardness, increased surface roughness and dental demineralization, as well as fracture toughness [4,5,12,[15][16][17]21,23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to take measures to minimize the possible adverse effects during the bleaching treatment [15]. The use of laser therapy can minimize tooth hypersensitivity by stimulating cell differentiation, increasing tissue repair and reducing inflammation.3 Calcium and / or fluoride can also be added to the composition of bleaching gels and the application of fluoride after treatment to reduce the risk of demineralization or loss of mineral enamel content [16,17,202].…”
Section: Introductionmentioning
confidence: 99%